The susceptibility of the rat pulmonary and caval vein myocardium to the catecholamine‐induced ectopy changes oppositely in postnatal development. (1st May 2021) - Kuzmin, Vlad S.; Ivanova, Alexandra D.; Potekhina, Viktoria M.; Samoilova, Daria V.; Ushenin, Konstantin S.; Shvetsova, Anastasia A.; Petrov, Alexey M.
Abstract : Key points: The developmental changes of the caval (SVC) and pulmonary vein (PV) myocardium electrophysiology are traced throughout postnatal ontogenesis. The myocardium in SVC as well as in PV demonstrate age‐dependent differences in the ability to maintain resting membrane potential, to manifest automaticity in a form of ectopic action potentials in basal condition and in responses to the adrenergic stimulation. Electrophysiological characteristics of two distinct types of thoracic vein myocardium change in an opposite manner during early postnatal ontogenesis with increased proarrhythmicity of pulmonary and decreased automaticity in caval veins. Predisposition of PV cardiac tissue to proarrhythmycity develops during ontogenesis in time correlation with the establishment of sympathetic innervation of the tissue. The electrophysiological properties of caval vein cardiac tissue shift from a pacemaker‐like phenotype to atrial phenotype in accompaniment with sympathetic nerve growth and adrenergic receptor expression changes. Abstract: The thoracic vein myocardium is considered as a main source for atrial fibrillation initiation due to its high susceptibility to ectopic activity. The mechanism by which and when pulmonary (PV) and superior vena cava (SVC) became proarrhythmic during postnatal ontogenesis is still unknown. In this study, we traced postnatal changes of electrophysiology in a correlation with the sympathetic innervation and adrenergic receptor distribution to reveal developmental differences in proarrhythmicity occurrence in PV and SVC myocardium. A standard microelectrode technique was used to assess the changes in ability to maintain resting membrane potential (RMP), generate spontaneous action potentials (SAP) and adrenergically induced ectopy in multicellular SVC and PV preparations of rats of different postnatal ages. Immunofluorescence imaging was used to trace postnatal changes in sympathetic innervation, β1‐ and α1A‐adrenergic receptor (AR) distribution. We revealed that the ability to generate SAP and susceptibility to adrenergic stimulation changes during postnatal ontogenesis in an opposite manner in PV and SVC myocardium. While SAP occurrence decreases with age in SVC myocardium, it significantly increases in PV cardiac tissue. PV myocardium starts to demonstrate RMP instability and proarrhythmic activity from the 14th day of postnatal life which correlates with the appearance of the sympathetic innervation of the thoracic veins. In addition, postnatal attenuation of SVC myocardium automaticity occurs concomitantly with sympathetic innervation establishment and increase in β1‐ARs, but not α1A‐AR levels. Our results support the contention that SVC and PV myocardium electrophysiology change during postnatal development, resulting in higher PV proarrhythmicity in adults. Key points: The developmental changes of the caval (SVC) and pulmonary vein (PV) myocardium electrophysiology are traced throughout postnatal ontogenesis. The myocardium in SVC as well as in PV demonstrate age‐dependent differences in the ability to maintain resting membrane potential, to manifest automaticity in a form of ectopic action potentials in basal condition and in responses to the adrenergic stimulation. Electrophysiological characteristics of two distinct types of thoracic vein myocardium change in an opposite manner during early postnatal ontogenesis with increased proarrhythmicity of pulmonary and decreased automaticity in caval veins. Predisposition of PV cardiac tissue to proarrhythmycity develops during ontogenesis in time correlation with the establishment of sympathetic innervation of the tissue. The electrophysiological properties of caval vein cardiac tissue shift from a pacemaker‐like phenotype to atrial phenotype in accompaniment with sympathetic nerve growth and adrenergic receptor expression changes.